Tradução e adaptação cultural do children with special health care needs screener - Arrué, Andrea Moreira (2012)
The study aimed to translate the Children with Special Health Care Needs-CSHCN Screener© into Portuguese, cultural adaptation and perform the test the reproducibility of the instrument. The process of translation and cultural adaptation was based on the stages of translation, back translation, committee review and pretesting. The scenario of the pretest was a teaching hospital and a ready local child care, located in southern Brazil, the subjects were relatives/caregivers of children aged zero to 12 years old, attending the services mentioned. The collection occurred from October, the statistical sample corresponded to 140 subjects and the selection was on demand service. It is concluded that the reproducibility of the instrument translated and adapted in this sample was satisfactory. The construct of translated and adapted version showed convergent validity with a measure of Cronbach Alpha and Kappa perfect agreement for all items evaluated. We conclude that the instrument CSHCN Screener© can be used in studies of the Portuguese language in Brazil. The prevalence of children with special health care needs was 36%, females (60%) were more vulnerable and the main demand was drug dependence (26%). The results of this research can subsidize the systematic survey and validated national demands of special needs health-SNH as well as provide an epidemiological profile of CSHCN. It is intended to contribute in knowledge of Nursing, recognizing this emerging clientele as health services, redirecting the guidelines and institutions working together to identify, monitor, perform reference and counter in health services. Similarly to other professionals, for this clientele requires intersectional action, since the SNH may cause or aggravate social and educational problems.